Feeding the cities: food supply and distribution - Argenti, Olivio (International Food Policy Research Institute, 2000)
Urban expansion and issues of food supply and distribution to and in the cities have four major consequences for urban food security. The first is the competition between demands for land needed for housing, industry, and infrastructure and land needed for agricultural production within and around cities... The second consequence is the increasing quantities of food that must be brought into cities and distributed within the expanding urban areas. This means more trucks coming into cities, contributing to traffic congestion and air pollution. It also means additional stress on existing food distribution infrastructure and facilities, most of which are already inefficient, unhygienic, and environmentally unfriendly... The third consequence is the modification of consumption habits and food purchasing behaviors. The final consequence for urban food security is the likelihood that low-income urban households will reside farther and farther away from food markets, often in slums that do not have water, roads, or electricity... City authorities need to adopt policies that support those involved in food supply and distribution activities by promoting private investment, getting involved in food supply and distribution themselves (by facilitating urban and peri-urban agriculture and by providing the necessary planning, infrastructure, facilities, services, information, and regulations), coordinating public and private development initiatives, and mediating between the central government and the private food sector. -- from Text